1998
DOI: 10.1128/mcb.18.3.1388
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Differential Coupling of Syk Family Kinases to the T-Cell Receptor: Reconstitution Studies in a ZAP-70-Deficient Jurkat T-Cell Line

Abstract: T-cell antigen receptor (TCR) engagement activates multiple protein tyrosine kinases (PTKs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
274
2
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(302 citation statements)
references
References 67 publications
23
274
2
1
Order By: Relevance
“…7D). To further explore the upregulation of CD69 surface expression by ORF5, we expressed ORF5 in Lck-deficient J.CaM1 cells, SLP-76-defient J14-v-29 cells, and ZAP70-deficient P116 cells, which were derived from Jurkat T cells (49,56,59). In contrast to its activity in parental Jurkat T cells, ORF5 expression was incapable of inducing the upregulation of CD69 surface expression in Lck-deficient J.CaM1 cells and SLP-76-defient J14-v-29 cells, indicating that Lck and SLP-76 are required for ORF5's ability to induce CD69 surface expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7D). To further explore the upregulation of CD69 surface expression by ORF5, we expressed ORF5 in Lck-deficient J.CaM1 cells, SLP-76-defient J14-v-29 cells, and ZAP70-deficient P116 cells, which were derived from Jurkat T cells (49,56,59). In contrast to its activity in parental Jurkat T cells, ORF5 expression was incapable of inducing the upregulation of CD69 surface expression in Lck-deficient J.CaM1 cells and SLP-76-defient J14-v-29 cells, indicating that Lck and SLP-76 are required for ORF5's ability to induce CD69 surface expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since Zap-70 is also required for TCRinduced PLCg1 phosphorylation (Williams et al, 1998(Williams et al, , 1999, one can speculate that Zap-70 itself is responsible for the phosphorylation of PLCg1. PLCg1, however, does not appear to be a direct substrate of Zap-70 (Veri et al, 2001) and no increase in Zap-70 phosphorylation or kinase activity has been observed in Jurkat cells expressing 70Z/3 Cbl (van Leeuwen et al, 1999a, b;Zhang et al, 1999a, b), making it unlikely that 70Z/3 Cbl alters the kinase activity of Zap-70.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence for a Zap-70 requirement in the effect of 70Z/3Cbl on PLCg1 phosphorylation was obtained by expressing WT PLCg1-HA together with either 70Z/3 Cbl or pCI-neo in the Zap-70-deficient Jurkat cell line P116 (Williams et al, 1998), and comparing the effect to that observed in P116 cells stably reconstituted with Zap-70. At equivalent levels of 70Z/3 Cbl expression, no PLCg1 phosphorylation was detected in either unstimulated or TCR-triggered P116 70Z/3 Cbl-induced NFAT activation requires Zap-70 but is independent of Slp-76…”
Section: The Effect Of 70z/3 Cbl On Plcg1 Phosphorylation Requires Zamentioning
confidence: 99%
See 2 more Smart Citations